Factors Affecting the Use of Long-Term Contraception - Aris Prastyoningsih; Anita Sri Sulistyowati; Juda Julia Kristiarini (Indonesian Journal of Global Health Research, 2023)
Indonesia's Total Fertility Rate is above the ASEAN average of 2.4 per 1000 Women of Reproductive Age and has continued to experience a stagnation period in the last 4 periods. In addition, the maternal mortality rate in Indonesia is still high at 359 per 100,000 live births. Long-Term Contraceptive Method is the most effective method of contraception to reduce birth rates but its users are only 20.3%. The national family planning program prioritizes the use of long-term contraceptive methods, but long-term contraceptive coverage is still low. This study aims to analyze the factors that influence the use of long-term contraception of the IUD type and implants at the Sang Timur Klaten Clinic. This type of research is quantitative research, with a research approach using a cross-sectional design with the research sample being couples of childbearing age using long-term contraception of the Implant and IUD type. The population in this study was 115 acceptors recorded in the register at the clinic. Non-random sampling technique used inclusion criteria. The inclusion criteria in this study are: Acceptors who are willing to be respondents, PUS who have followed long-term contraceptive methods. Data analysis with Chi-Square with a confidence level of 95%. The results of the bivariate analysis in this study used the Chi-Square test and the multivariate test used logistic regression. The results showed that there was a relationship between age, education and menstrual history with the use of long-term contraceptive methods with a p value <0.05. There is no relationship between work, parity, husband's support and family income with the use of long-term contraceptive methods with a p value > 0.05. The most dominant factor with long-term contraceptive use is education.